Working together to address global problems: Royal Geographical Society (with IBG) Medals and Awards ceremony 2014. Issue 3 (September 2014) - Rees, Judith; Boulton, Geoffrey; Rosling, Hans; Smith, Susan J; Kothari, Uma; Dearing, John
<x xml:space="preserve">Abstract</x> The Royal Geographical Society (with IBG)'s annual Medals and Awards recognise achievements in researching, communicating and teaching a wide range of geographical knowledge. The speeches and citations are a record of the ceremony of 2014 with comments by Hans Rosling and Professors Geoffrey Boulton, Susan J Smith, Uma Kothari and John Dearing. The speeches encompass communicating geographical data, glaciology, environmental change, human geography and global development.